Influence of nitric oxide and phosphodiesterases during in vitro maturation of bovine oocytes on meiotic resumption and embryo production. Issue 3 (27th June 2017) - Botigelli, Ramon Cesar; Schwarz, Katia Lancellotti; Zaffalon, Fabiane Gilli; Del Collado, Maite; Castro, Fernanda Cavallari; Fernandes, Hugo; Leal, Claudia Lima Verde
Summary: This study aimed to examine the effects of nitric oxide (NO) and different phosphodiesterase (PDE) families on meiosis resumption, nucleotides levels and embryo production. Experiment I, COCs were matured in vitro with the NO donor S -nitroso- N -acetylpenicillamine (SNAP) associated or not with the soluble guanylate cyclase (sGC) inhibitor 1H-[1, 2, 4]oxadiazolo[4, 3-a]quinoxalin-1-one (ODQ), meiotic resumption and nucleotides levels were assessed. SNAP delayed germinal vesicle breakdown (GVBD) (53.4 ± 1.2 versus 78.4 ± 2.4% for controls, P < 0.05) and ODQ reversed its effect (73.4 ± 6.3%, P > 0.05). Cyclic GMP levels were higher in SNAP (3.94 ± 0.18, P < 0.05) and ODQ abolished the effect (2.48 ± 0.13 pmol/COC, P < 0.05), while cAMP levels were decreased in both treatments. Experiment II, COCs were cultured with SNAP alone or with PDEs inhibitors. SNAP alone or with PDEs inhibitors delayed GVBD (24.7 ± 2.8 to 56.9 ± 8.7%, P < 0.05) compared with the control (77.1 ± 1.8%), and SNAP and SNAP + cilostamide had lowest rates (34.9 ± 9.2% and 24.7 ± 2.8%). Experiment III, COCs were cultured (24–28 h) with SNAP and SNAP + cilostamide to assess metaphase II (MII) rates and embryo production. SNAP + cilostamide (50.0 ± 2.0%, P < 0.05) had lower MII rates at 24 h in vitro maturation (IVM), but at 28 h all groups were similar (66.6 to 71.4%, P > 0.05). Embryo development did not differ from the control for SNAP and cilostamide groups (38.7 ± 5.8, 37.9 ± 6.2 and 40.5 ± 5.8%, P > 0.05), but SNAP + cilostamide decreased embryo production (25.7 ± 6.9%, P < 0.05). In conclusion, SNAP was confirmed to delay meiosis resumption by the NO/sGC/cGMP pathway, by increasing cGMP, but not cAMP. Inhibiting different PDEs to further increase nucleotides in association with SNAP did not show any additive effects on meiosis resumption, indicating that other pathways are involved. Moreover, SNAP + cilostamide affected the meiosis progression and decreased embryo development.